Thematic role assignment in non-default verb classes: A cross-linguistic comparison of English and German - Kyriaki, Louise; Schlesewsky, Matthias; Bornkessel-Schlesewsky, Ina (Glossa (London), 2021)
The influence of sentential cues (such as animacy and word order) on thematic role interpretation differs as a function of language (MacWhinney et al. 1984). However, existing cross-linguistic research has typically focused on transitive sentences involving agents, and interpretation of non-default verb classes is less well understood. Here, we compared the way in which English and German native speakers – languages known to differ in the cue prominence of animacy and word order – assign thematic roles. We compared their interpretation of sentences containing either default (agent-subject) or non-default (experiencer-subject) verb classes. Animacy of the two noun phrases in a sentence was either animate-inanimate and plausible (e.g. “The men will devour the meals...”) or inanimate-animate and implausible in English (e.g. “The meals will devour the men...”). We examined role assignment by probing for either the actor or undergoer of the sentence. Mixed effects modelling revealed that role assignment was significantly influenced by noun animacy, verb class, question type, and language. Results are interpreted within the Competition Model framework (Bates et al. 1982; MacWhinney et al. 1984) and show that English speakers predominantly relied on word order for thematic role assignment. German speakers relied on word order to a comparatively lesser degree, with animacy a prominent cue. Cue weightings appeared to be modulated in the context of other cues, with the weighting of an animacy-based strategy over a word-order-based strategy increasing for sentences with non- default (experiencer-subject) verbs and with undergoer-focused questions, particularly where word order was more flexible (i.e. in German as opposed to English). These findings highlight the differential influence of the surrounding context (e.g. question focus) across languages.